2010
DOI: 10.1128/iai.01433-09
|View full text |Cite
|
Sign up to set email alerts
|

TheBrucella abortusPhosphoglycerate Kinase Mutant Is Highly Attenuated and Induces Protection Superior to That of Vaccine Strain 19 in Immunocompromised and Immunocompetent Mice

Abstract: Brucella abortus is a facultative intracellular bacterial pathogen that causes abortion in domestic animals

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 39 publications
1
29
0
Order By: Relevance
“…Our research group has previously demonstrated the virulence of the vaccine strains S19 and RB51 in IRF-1 KO mice. Only 70 to 80% of IRF-1 KO mice inoculated with S19 at 10 6 CFU survived the first 4 weeks after infection, while all mice inoculated with RB51 at 10 6 or 10 8 CFU survived the first 4 weeks (21,26). Our data suggest the following order of virulence in IRF-1 KO mice: the S2308 strain Ͼ ⌬omp19:: kan strain Ͼ ⌬mfp::kan strain.…”
Section: Resultsmentioning
confidence: 68%
See 4 more Smart Citations
“…Our research group has previously demonstrated the virulence of the vaccine strains S19 and RB51 in IRF-1 KO mice. Only 70 to 80% of IRF-1 KO mice inoculated with S19 at 10 6 CFU survived the first 4 weeks after infection, while all mice inoculated with RB51 at 10 6 or 10 8 CFU survived the first 4 weeks (21,26). Our data suggest the following order of virulence in IRF-1 KO mice: the S2308 strain Ͼ ⌬omp19:: kan strain Ͼ ⌬mfp::kan strain.…”
Section: Resultsmentioning
confidence: 68%
“…Previous studies from our laboratory have identified genes related to survival and virulence in B. abortus (13,14,21,26). Here, we investigated the importance of the Brucella proteins Mfp and Omp19 in microbial pathogenesis by evaluating the persistence of the B. abortus gene replacement ⌬omp19::kan and ⌬mfp::kan mutant strains both intracellularly and in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations